PENGARUH MEDIA PUZZLE PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KREATIVITAS DAN PEMIKIRAN ALTERNATIF SISWA SD/MI - Aulia, Lutfi; Suhaila Lubis , Nabila (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
This research aims to increase elementary/MI students' creativity and alternative thinking in mathematics subjects using puzzle media. This research uses qualitative descriptive research with a library study method, which is carried out directly and carries out research to find out what actually happens with various problems and has research subjects, namely 10 children at grade 5 elementary school level. The implementation time is two days from the 11th. - 12 December 2023. The results of the research show that puzzle media has been proven to increase the creativity and alternative thinking of elementary/MI students, as well as teacher performance. Puzzel media is very useful for any learning, including learning mathematics, which children can easily understand.